the trumpet of the swam - White E.B (New York Harpercollins childrens book, 1970)
Like the rest of his family, Louis is a trumpeter swan. But unlike his four brothers and sisters, louis can't trumpet joyfully. In fact, He can even make a sound. And since he can't trumpet his love, the beautiful swan serena pays absolutely no attention to him. Louis tries everything he can think of to win serena's affection he even goes to school to learn to read and write. But nothing seems to work. Then his father steals him a real brass trumpet. Is a musical instrument the key to winning louis his love?
English